Potential of Boiler Ash from 30 and 60 Ton/Hour Palm Oil Mills as a Nutrient Source in Palm Plantation - Gita Rohani Br. Pardede; Ika Ucha Pradifta Rangkuti (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The palm oil industry generates large amounts of biomass waste, one of which is boiler ash produced from the combustion of fiber and shell in palm oil mill boilers. Boiler ash is generally underutilized and is commonly stockpiled around factory areas, potentially causing environmental pollution. This study aimed to evaluate the potential of boiler ash from palm oil mills (POM) with capacities of 30 ton/hour and 60 ton/hour as a nutrient source for oil palm plantations. The research employed a quantitative descriptive method using mass balance analysis, laboratory analysis, and Independent Samples T-Test. The results showed that the 60 ton/hour POM produced a higher amount of boiler ash, reaching 16,712.75 tons, compared to 8,624.40 tons from the 30 ton/hour POM. Boiler ash from the 30 ton/hour POM had a higher Nitrogen content of 0.36%, while boiler ash from the 60 ton/hour POM contained higher levels of Potassium (4.79%), Phosphorus (2.17%), Magnesium (2.70%), and Calcium (6.87%). Statistical analysis indicated that most nutrient parameters showed significant differences at the 5% significance level. Boiler ash has strong potential to be utilized as an alternative nutrient source to support sustainable oil palm plantation systems and reduce dependence on inorganic fertilizers.